IMPLEMENTASI KURIKULUM MERDEKA DALAM PENGEMBANGAN KARAKTER SISWA DI TINGKAT SEKOLAH DASAR - Firsta Bagus Sugiharto; Wahyu Widodo; Kardiana Metha Rozhana; Permince Baba Mollu (Inteligensi : Jurnal Ilmu Pendidikan, 2023)
This research aims to find out how the implementation of the Merdeka Curriculum at the elementary school level affects the character of students in class IV of SD Negeri 1 Landungsari Regency through case study research. The instruments used are observation, interviews, documentation, analyzing data by reducing data, presenting data and drawing conclusions followed by data triangulation. The results of the research showed that the Merdeka Curriculum can influence students' independent character through activities in the classroom during the learning process and external activities such as school extracurricular activities and participating in competitions outside of school. Apart from implementing independent character, students can practice responsibility for their mandate and task given to students. Student character development activities can run well with cooperation between elements of the school community including students, teachers, parents and the community around the school